Strategi Kampanye Politik Anies Baswedan dalam Membangun Citra Politik Pada Pemilihan Presiden Tahun 2024 - Aryadillah, Aryadillah; Fitriansyah , Fifit (LPPM Universitas Bina Sarana Informatika, 2022)
The existence of this political space of course makes various political parties carry the champions of their respective parties. If you look at the existing competition, then of course various political parties use their weapons with various existing political strategies to win votes and gain public sympathy in building their political image. Ahead of the Indonesian Presidential General Election in 2024 is a democratic process to elect the President and Vice President of the Republic of Indonesia for the period 2024–2029. A modest democratic party carried out through the presidential election in 2024, is considered by a number of political observers to be an attractive competition. This can be seen from each party candidate carrying out a presidential candidate in various strategies carried out to attract public sympathy, one of which is presidential candidate Anies Baswedan. The purpose of this study is to examine the various political campaign strategies carried out by Anies Baswedan in the 2024 presidential election. The method used is a qualitative approach by examining data based on media sources and relevant references. The results of this study are based on the results of the Populi Center ranking Anies in first place as much as 29.0% based on open questions given to the public at random. Thus, if you look at the graph above, Anies Baswedan has the most public sympathy in building his political image in winning the 2024 presidential election. Keyword: Political Campaign Strategy, Political Image